Medium Access Control layer protocol design based on stochastic network calculus for underwater wireless communication in open‐ocean fish farming. (14th February 2022) - Saravanan, M.; Sukumaran, Rajeev; Radhakrishnan, M.; Christhuraj, M.R.; Manikandan, T.T.
Summary: The usage of the underwater communication channel and medium access control (MAC) layer protocol architecture is the most problematic aspect of a seawater wireless communication network. The underwater acoustic wireless communication is a highly appealing choice for information transfer in the communication medium. However, calculating the deferral rate for transmitting real‐time traffic is a challenging task in the underwater environment. Therefore, it introduces the research challenges related to underwater communication, especially throughput and transmission deferral. This research work investigates an MAC protocol U‐TDMA with multi‐hop worst‐case delay analysis for different flow and relays. This research intended to compare the execution of the U‐TDMA protocol with stochastic network calculus (SNC) and without SNC. The U‐TDMA‐wireless protocol establishes the connection and forwards the fish‐mandated information to the mobile sink with the help of upper layers. Also, it improves interface efficiency by taking account of the lengthy delay time of the underwater acoustic channel and addressing difficulties connected to the terminal. Abstract : The paper proposes the U‐TDMA protocol for different flow and relay. The proposed work for open‐ocean fish farming is analyzed with SNC. The algorithm for super frame time slots plays an essential role in the relay between the intended nodes. Therefore, U‐TDMA is well suited for open‐ocean fish farming to transmit acoustic information to the base station. Furthermore, this protocol produces a high delivery rate and low frame loss and compares the delay variations with SNC.